INDONESIAN L2 LEARNERS’ ATTITUDES TOWARDS GROUP WORK: A SURVEY STUDY ON GENDER DIFFERENCES - Aulita, Janice; Subekti, Adaninggar Septi (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2024)
This study was conducted to investigate the possible interaction between the attitudes of Indonesian learners from non-English majors towards group work in the English as second/foreign (L2) classes and their gender. The study employed an online survey. In this study, 187 learners from various regions in Indonesia participated. The study found that learners generally reported positive attitudes towards group work to facilitate a better learning atmosphere, for their self-improvement, and a medium of learning with their classmates. Furthermore, this study found no statistically significant difference in their attitudes towards group work seen from their gender. The no significant difference indicates that both male and female learners reported relatively similar attitudes towards group work. Limitations are acknowledged, and the possible contributions and pedagogical implications are stated alongside suggested directions for future studies in the fields of gender and group work in L2 classes.